Effects of rosiglitazone on the serum paraoxonase activity and metabolic parameters in patients with type 2 diabetes - Atamer, A.; Selek, S.; Kocyigit, Y.; Ilhan, N.; Sen, T.; Atamer, Y. (Elsevier Ireland Ltd, 2007)
[Abstract Not Available]
76th Congress of the European-Atherosclerosis-Society -- JUN 10-13, 2007 -- Helsinki, FINLAND